ANALISIS CURAH HUJAN SEBAGAI UPAYA MEMINIMALISASI DAMPAK KEKERINGAN DI KABUPATEN GUNUNG KIDUL TAHUN 2014 - Farida Apriani; Yuliani Dwi Setianingsih; Umi Muntiah Prismaning Arum; Kartika Ari Susanti; Saptian Imam Wicaksono; Abdul Faruk (Khazanah: Jurnal Mahasiswa, 2014)
Research has been conducted to predict the rainfall by 2013 to minimize drought in Gunungkidul with the purpose to know the predictions of rainfall in GunungKidul Regency in September until December 2013 as well as knowing how to minimize drought in GunungKidul Regency. The Data used in this study are precipitation data from 15 posts in Gunungkidul Regency in January 2009 – December 2013 obtained from Agency for meteorology Climatology and Geophysics (BMKG) D.I.Yogyakarta. The analysis used in this study by using Desktiptif Analysis and decomposition of Seasonal prediction value and generate rainfall in Gunungkidul Regency in September until December 2013 respectively is 98, 448mm, 152,426 mm, 223,112 mm, 360,278 mm. from the results of this prediction can be done the anticipation for the year 2014.